1) - 16
2) утверждение справедливо для любого значения х
3) 0,95
Объяснение:
1) 3/4х-13=1/8х-23
3/4х-1/8х=-23+13
5/8х=-10
х=-10:5/8
х=-16
2) 18-2x=4x-6(x-3)
18-2х=4х-6х+18
-2х=4х-6х
-2х=-2х
утверждение справедливо для любого значения х
3) 5-5x=2,5(2x-1)-2
5-5x=5х-2,5-2
5-5x=5х-4,5
-5х-5x=-4,5-5
-10х=-9,5
х=-9,5:(-10)
х=0,95
1) - 16
2) утверждение справедливо для любого значения х
3) 0,95
Объяснение:
1) 3/4х-13=1/8х-23
3/4х-1/8х=-23+13
5/8х=-10
х=-10:5/8
х=-16
2) 18-2x=4x-6(x-3)
18-2х=4х-6х+18
-2х=4х-6х
-2х=-2х
утверждение справедливо для любого значения х
3) 5-5x=2,5(2x-1)-2
5-5x=5х-2,5-2
5-5x=5х-4,5
-5х-5x=-4,5-5
-10х=-9,5
х=-9,5:(-10)
х=0,95